Exacerbation of Methamphetamine Neurotoxicity in Cold and Hot Environments: Neuroprotective Effects of an Antioxidant Compound H-290/51 - Sharma H.S.; Kiyatkin E.A.; Patnaik R.; Lafuente J.V.; Muresanu D.F.; Sjöquist P.-O.; Sharma A. (My University, 2025)
In this study, we examined the influence of cold and hot environments on methamphetamine (METH) neurotoxicity in both drug-naive rats and animals previously exposed to different types of nanoparticles (NPs). Since METH induces oxidative stress, we also examined how a potential chain-breaking antioxidant H-290/51 (Astra-Zeneca, Mölndal, Sweden) affects METH-induced neurotoxicity. Exposure of drug-naive rats to METH (9 mg/kg, s.c.) at 4, 21, or 34 °C for 3 h resulted in breakdown of the blood-brain barrier (BBB), brain edema, and neuronal injuries, which all differed in severity depending upon ambient temperatures. The changes were moderate at 21 °C, 120–180 % larger at 34 °C, and almost absent at 4 °C. In rats chronically treated with NPs (SiO2, Cu, or Ag; 50–60 nm, 50 mg/kg, i.p. for 7 days), METH-induced brain alterations showed a two- to fourfold increase at 21 °C, a four- to sixfold increase at 34 °C, and three- to fourfold increase at 4 °C. SiO2 exposure showed the most pronounced METH-induced brain pathology at all temperatures followed by Ag and Cu NPs. Pretreatment with a potent antioxidant compound H-290/51 (50 mg/kg, p.o., 30 min before METH) significantly reduced brain pathology in naive animals exposed to METH at 21 and 34 °C. In NPs-treated animals, however, attenuation of METH-induced brain pathology occurred only after repeated exposure of H-290/51 (−30 min, 0 min, and +30 min). These observations are the first to show that NPs exacerbate METH-induced brain pathology in both cold and hot environments and demonstrate that timely intervention with antioxidant H-290/51 could have neuroprotective effects. © 2015, Springer Science+Business Media New York.